Forgotten roots of the Nordic welfare state in Protestant cultures - Mohnike, Thomas 1974-; Hjortshøj, Søren Blak 1979- (Brepols, 2025)
"The Nordic welfare state of the 20th century has been hailed around the world as a model of how to build democratic and egalitarian societies. It has often been described as a project of social democracy, often following a narrative of secularization and rationalization of society. However, some of the most important actors and ideas of the "Scandinavian Sonderweg" had their roots in Protestant, often Pietist and revivalist milieus that dreamed of creating an egalitarian community. The present volume explores these often forgotten roots in several case studies of phenomena from the seventeenth to the twenty-first century, focusing primarily on questioning the function of aesthetics in the creation of the welfare state model. We argue that aesthetics and what Friedrich Schiller called aesthetic education played an important, unifying role for Nordic societies. These aesthetics were shaped by Protestant ideas and practices. Through references to the then widespread circulation of educational texts based on Luther's catechism, the later pietistic catechism of Erik Pontoppidan, Nordic hymnbooks, and practices such as communal singing and preaching in church, church coffee, reading circles, and conventicle meetings, a common aesthetic language emerged that unified different social groups and their competing goals and claims. Civic actors and movements learned specific ways to engage in society, to develop practices of internalizing responsibility, (self)critique, and accountability, and to communicate and develop a more democratic modern civic sphere. We therefore propose to look at this history from the perspective of a historically changing aesthetic as an integrating principle for understanding the political, social, cultural, economic and many other aspects of the Nordic welfare state. "
Keywords: Aufsatzsammlung